EFEKTIVITAS METODE STORYTELLING DALAM MENUMBUHKAN MINAT BELAJAR SKI DI UPTD SPF SDN BLOK VI BARU - Juwita Ayu Putri; Susi Fitriani (Jurnal Pendidikan Nusantara, 2024)
This study aims to determine the effectiveness of the storytelling method in fostering students' interest in learning Islamic Cultural History (SKI) at UPTD SPF SDN Blok VI Baru. This study utilised a Classroom Action Research (CAR) approach conducted in two cycles, with 28 fifth-grade students as research subjects. The instruments used included observation sheets, learning interest questionnaires, and reflection notes. The results showed that the storytelling method was able to significantly increase students' interest in learning. In cycle I, the percentage of students who showed high interest in learning was only 65%, but this increased to 88% in cycle II. Students were more enthusiastic, actively asked questions, and showed full attention to the material presented through stories. Thus, the storytelling method can be an alternative SKI learning strategy to create a fun learning atmosphere while fostering students' love for Islamic history.